2006
DOI: 10.1007/s10741-006-0234-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel and potential future biomarkers for assessment of the severity and prognosis of chronic heart failure

Abstract: Over the last two decades, the pathophysiology and biomolecular basis of heart failure syndrome has reached sound and more comprehensive understanding. This knowledge has allowed expert researchers and clinicians to explore an entirely new spectrum of potential biochemical markers derived from different cellular and signaling pathways that lead to myocardial hypertrophy, chronic damage of the myocyte, apoptosis, and, ultimately, myocardial remodeling. Indeed, the link between myocardial remodeling and adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 127 publications
(113 reference statements)
1
20
0
Order By: Relevance
“…Sp1 is an oncoprotein that is critically involved in cell growth regulation and overexpresses during tumorigenesis. Recent studies also consistently demonstrated elevations of Sp1 levels in cardiac hypertrophy resulted from increased left-right shunting, volume loading of the left ventricle, pressure loading of the right ventricle, or angiotensin II stimulation [25][26][27]. In agreement with these previous studies, we also found a robust increase in Sp1 expression in left ventricular hypertrophy (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Sp1 is an oncoprotein that is critically involved in cell growth regulation and overexpresses during tumorigenesis. Recent studies also consistently demonstrated elevations of Sp1 levels in cardiac hypertrophy resulted from increased left-right shunting, volume loading of the left ventricle, pressure loading of the right ventricle, or angiotensin II stimulation [25][26][27]. In agreement with these previous studies, we also found a robust increase in Sp1 expression in left ventricular hypertrophy (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, to confirm that the myocytes treated with angiotensin II indeed developed hypertrophic conditions, we measured the changes of cell size and expression of several biomarkers for cardiac hypertrophy including ␤-MHC, MLC-2, and ANF (38). As depicted in Fig.…”
Section: Role Of Mir-1 and Mir-133 In Overexpression Of F-channel Genmentioning
confidence: 94%
“…Novel biomarkers for individualized therapy are currently under intensive investigation and may improve the clinical outcome of heart failure (HF) patients. 2,3 So far, the largest wealth of knowledge lies with measurement of b-type natriuretic peptide (BNP), which has been shown to improve clinical outcome in HF patients. 4 A hallmark of CHF is the development of myocardial remodeling and interstitial fibrosis, resulting in changes in the extracellular matrix (ECM).…”
mentioning
confidence: 99%